2008
DOI: 10.1186/1757-1146-1-s1-o2
|View full text |Cite
|
Sign up to set email alerts
|

Clawed toes in the diabetic foot: neuropathy, intrinsic muscle volume, and plantar aponeurosis thickness

Abstract: Table 1: Intrinsic muscle volume (mean ± SD) claw toes yes claw toes no neuropathy yes 0.130 ± 0.037 0.191 ± 0.008 neuropathy no 0.198 ± 0.018 0.192 ± 0.034 Publish with Bio Med Central and every scientist can read your work free of charge "BioMed Central will be the most significant development for disseminating the results of biomedical researc h in our lifetime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…A study conducted by Ledoux et al . found that a neuropathic foot with claw toes has less intrinsic muscle volume than non‐neuropathic groups and suggested that both intrinsic muscle atrophy and plantar fascia dysfunction lead to the development of claw toes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study conducted by Ledoux et al . found that a neuropathic foot with claw toes has less intrinsic muscle volume than non‐neuropathic groups and suggested that both intrinsic muscle atrophy and plantar fascia dysfunction lead to the development of claw toes.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Ledoux et al 15 found that a neuropathic foot with claw toes has less intrinsic muscle volume than non-neuropathic groups and suggested that both intrinsic muscle atrophy and plantar fascia dysfunction lead to the development of claw toes. Even then, Bus et al 21 concluded that intrinsic muscle atrophy and muscle imbalance are significant for the development of claw toe deformity in the diabetic foot.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At least 15% of these ulcerations would lead to some forms of foot amputation. Previous study found that early diabetic foot tends to be toes deformities [ 7 9 ] and imbalance in the muscles to the foot or lower extremity [ 10 ], then causing abnormal plantar pressure [ 11 ]. When the lesion or dysfunction of the human foot structure and human locomotion ability deteriorated, plantar pressure and foot loading distribution would change consequently [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%